Magnetic charged particles of optical spherical antiferromagnetic model with fractional system - Yao, Shao-Wen; Korpinar, Talat; Baleanu, Dumitru; Korpinar, Zeliha; Almohsen, Bandar; İnç, Mustafa (De Gruyter Poland Sp Z O O, 2021)
In this article, we first consider approach of optical spherical magnetic antiferromagnetic model for spherical magnetic flows of Upsilon-magnetic particle with spherical de-Sitter frame in the de-Sitter space S-1(2). Hence, we establish new relationship between magnetic total phases and spherical timelike flows in de-Sitter space S-1(2). In other words, the applied geometric characterization for the optical magnetic spherical antiferromagnetic spin is performed. Moreover, this approach is very useful to analyze some geometrical and physical classifications belonging to Upsilon-particle. Besides, solutions of fractional optical systems are recognized for submitted geometrical designs. Geometrical presentations for fractional solu-tions are obtained to interpret the model. These obtained results represent that operation is a compatible and sig-nificant application to restore optical solutions of some fractional systems. Components of models are described by physical assertions with solutions. Additionally, we get solutions of optical fractional flow equations with designs of our results in de-Sitter space S-1(2).
Keywords: Upsilon-magnetic particle; geometric phase; optical fiber; evolution equations; traveling wave hypothesis; antiferromagnetic